Fulvic Acid from Oil Palm Empty Fruit Bunches as Feed Additive Improves Digestive Tract and Intestinal Morphology in Broilers: Aditif Pakan Asam Fulvat Tandan Kosong Kelapa Sawit untuk Memperbaiki Saluran Pencernaan dan Morfologi Usus pada Ayam Pedaging - Dimawarnita, Firda; Dwi Margi Suci; Mugia Reksa Wicaksari; Yora Faramitha; Erwinsyah, Fayyadh Altamis; Donny Nugroho Kalbuadi; Didiek Hadjar Goenadi; Komang Gede Wiryawan; Arif Darmawan (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2025)
The use of Antibiotic Growth Promoters (AGPs) in the poultry industry led to farmers’ dependence on antibiotics. Therefore, a safer alternative feed additive, such as fulvic acid, was needed. This study aimed to evaluate the effectiveness of fulvic acid extracted from oil palm empty fruit bunches (FA-OPEFB) as a feed additive on broiler chickens’ digestive tract and intestinal morphology. A total of 150 broiler chickens were used in a Completely Randomized Design (CRD) consisting of three treatments and five replications: P0 (drinking water without FA-OPEFB), P1 (drinking water with 0.1% FA-OPEFB), and P2 (drinking water with 0.2% FA-OPEFB). Observed variables included the relative weight and length of the digestive tract and intestinal morphology. The results showed that the addition of FA-OPEFB in drinking water significantly affected the ileum percentage, villus height, crypt depth, and villus surface area. It was concluded that 0.2% FA-OPEFB in drinking water reduced the relative weight and length of the ileum and improved intestinal morphology in broiler chickens. Key words: broiler chicken, digestive tract, fulvic acid, intestinal morphology, OPEFB